Correction to: Study of serum sclerostin levels and its role in vascular calcification in patients with chronic kidney disease - Ahmed R. Elarbagy; Yassein S. Yassein; Mahmoud M. Emara; Ahmed A. Sonbol; Khaled M. A. Elzorkany; Amera A. Sharaf El Deen (SpringerOpen, 2022)
An amendment to this paper has been published and can be accessed via the original article.